Fighting austerity: why after 80 years the General Theory is still relevant today - Marcuzzo, Maria Cristina (Brazilian Keynesian Review, 2017)
In the aftermath of the 2007-8 crisis, the name of Keynes has again entered the list of economists to be read, whose ideas are to be taken seriously. After over twenty-five years of ostracism, spent praising the efficiency of free markets and running econometric tests to prove that economic policies are either ineffectual or even irrelevant, there has been an upsurge in the wave of references to Keynes in the media. Unfortunately, this has not been reflected in the academic scene, still dominated by the macroeconomics of anti- or pre-Keynesian inspiration that took hold between the 1970s and 1980s.